Effect of Remedial Teaching Programme in Science on Academic Achievement of Students Studying in Class VII - Arora, Anita (JOURNAL OF TEACHER EDUCATION AND RESEARCH, 2012)
Remedial teaching can be considered as an effective correction technique, a programme to improve teaching learning process and an instruction for overcoming difficulties and misconceptions in various subjects. The studies revealed that Remedial Instructions Materials were effective in improving academic attainment of students. Therefore, the present study was aimed at assessing the effect of remedial teaching programme in science on academic achievement of students studying in class VII. According to the nature of the study Quasi- Experimental method has been used; one school as the sample was selected by the simple random sampling technique. In the school, there were 44 students in class VII. Researcher selected only those students among these students who scored below 40% in Science achievement test. Sixteen students were selected for the purpose of the study through the purposive sampling method. The remedial teaching was independent variable while academic achievement was dependent variable. For measuring academic achievement, Science achievement test was constructed by investigator and for remedial teaching a diagnostic test was prepared by the researcher herself according to the specific need of students. To analyse data ‘t’ test was used,the result of the study revealed that remedial teaching programme was effective in developing academic achievement of the students who received the treatment.